A Functional Switch of NuRD Chromatin Remodeling Complex Subunits Regulates Mouse Cortical Development - Justyna Nitarska; Jacob G. Smith; William T. Sherlock; Michele M.G. Hillege; Alexi Nott; William D. Barshop; Ajay A. Vashisht; James A. Wohlschlegel; Richard Mitter; Antonella Riccio (Cell Reports, 2016)
Histone modifications and chromatin remodeling represent universal mechanisms by which cells adapt their transcriptional response to rapidly changing environmental conditions. Extensive chromatin remodeling takes place during neuronal development, allowing the transition of pluripotent cells into differentiated neurons. Here, we report that the NuRD complex, which couples ATP-dependent chromatin remodeling with histone deacetylase activity, regulates mouse brain development. Subunit exchange of CHDs, the core ATPase subunits of the NuRD complex, is required for distinct aspects of cortical development. Whereas CHD4 promotes the early proliferation of progenitors, CHD5 facilitates neuronal migration and CHD3 ensures proper layer specification. Inhibition of each CHD leads to defects of neuronal differentiation and migration, which cannot be rescued by expressing heterologous CHDs. Finally, we demonstrate that NuRD complexes containing specific CHDs are recruited to regulatory elements and modulate the expression of genes essential for brain development.